Detection of Oral Testosterone Undecanoate Administration in UGT2B17 del/del and del/ins Individuals. Part I: Urinary Steroid Profile and IRMS Markers - Coll, Sergi; Shiomura, Sho; Alechaga, Élida; Bressan, Claudia; Monfort, Núria; Ventura, Rosa; Okano, Masato (Drug testing and analysis, 2025)
The detection of endogenous anabolic androgenic steroids misuse in Asian population using the Steroidal Module of the Athlete Biological Passport (ABP) is a challenge due to the high prevalence of UGT2B17 gene deletion polymorphism and low levels of testosterone (T) glucuronide. In this study, the capabilities of different approaches based on urine analysis for detecting oral T undecanoate administration were evaluated in 13 Asian volunteers, including 11 subjects with del/del genotype and 2 subjects with del/ins genotype. In this part of the work, the effect on the urinary steroid profile (SP) and the isotope ratio mass spectrometry (IRMS) markers were studied. Results showed that the 5α-androstane-3α,17β-diol/epitestosterone ratio is the most sensitive marker of the SP to detect oral T administration in Asian volunteers. All urines that led to suspicious urinary SP were concluded IRMS positive. However, for some subjects, the ABP Steroidal Module was unable to identify suspicious samples that were still detectable by IRMS. Positive IRMS samples were detected up to 24 h (n = 9), 36 h (n = 3), or 48 h (n = 1) after oral administration. Overall, the urinary SP together with IRMS allowed the detection of T administration in Asian volunteers. However, the detection windows are short, as reported for oral T administration in Caucasian volunteers. These findings highlight the need of implementing additional markers in the Steroidal Module of ABP that could enlarge detection windows.